O canto crossover: uma revisão bibliográfica e estudos de relações possíveis na performance da música vocal brasileira. - Helen Isolani Marques (2019)
The main objective of this work is to point out bibliographic references that help in understanding the meanings of the term crossover in music so that relationships can be established between this style and its manifestation in Brazilian vocal music. The work considers that such understanding can lead to the success in performance and valorization of the Brazilian performer against crossover music as a plural artist, both for his understanding of different musical languages and for the result of his multidisciplinary artistic work. To achieve this goal, studies were conducted on the term crossover, according to historical, interpretative and market perspectives. To aid and develop a broader understanding of the term, the concept of hypertext and the recognition of its properties were also used, analogous to the artistic practice of crossover. From a hypertext perspective, a crossover show, for example, can be configured as a network of multiple connections, connecting popular and erudite works of art, performers with various skills, current and ancient technologies and, above all, diverse audiences. Concepts such as hybridity, multistylism and globalization.